Neural correlates of suspiciousness and interactions with anxiety during emotional and neutral word processing - Fisher, Joscelyn E.; Miller, Gregory A.; Sass, Sarah M.; Silton, Rebecca Levin; Edgar, J. Christopher; Stewart, Jennifer L.; Zhou, Jing; Heller, Wendy (Frontiers in Psychology, 2014)
Suspiciousness is usually classified as a symptom of psychosis, but it also occurs in depression and anxiety disorders. Though how suspiciousness overlaps with depression is not obvious, suspiciousness does seem to overlap with anxious apprehension and anxious arousal (e.g., verbal iterative processes and vigilance about environmental threat). However, suspiciousness also has unique characteristics (e.g., concern about harm from others and vigilance about social threat). Given that both anxiety and suspiciousness have been associated with abnormalities in emotion processing, it is unclear whether it is the unique characteristics of suspiciousness or the overlap with anxiety that drive abnormalities in emotion processing.. Event-related brain potentials were obtained during an emotion-word Stroop task. Results indicated that suspiciousness interacts with anxious apprehension to modulate initial stimulus perception processes. Suspiciousness is associated with attention to all stimuli regardless of emotion content. In contrast, anxious arousal is associated with a later response to emotion stimuli only. These results suggest that suspiciousness and anxious apprehension share overlapping processes, but suspiciousness alone is associated with a hyperactive early vigilance response. Depression did not interact with suspiciousness to predict response to emotion stimuli. These findings suggest that it may be informative to assess suspiciousness in conjunction with anxiety in order to better understand how these symptoms interact and contribute to dysfunctional emotion processing.